Neighbourhood perceptions of physical activity: a qualitative study - Coleman Rosarie; Woods Catherine; Burgoyne Louise N; Perry Ivan J (BMC, 2008)
Abstract Background Effective promotion of physical activity in low income communities is essential given the high prevalence of inactivity in this sector. Methods This study explored determinants of engaging in physical activity in two Irish city based neighbourhoods using a series of six focus groups and twenty five interviews with adult residents. Data were analysed using constant comparison methods with a grounded theory approach. Results Study findings centred on the concept of 'community contentment'. Physical activity was related to the degree of contentment/comfort within the 'self' and how the 'self' interacts within the neighbourhood. Contemporary focus on outer bodily appearance and pressure to comply with societal expectations influenced participants' sense of confidence and competence. Social interaction, involvement, and provision of adequate social supports were viewed as positive and motivating. However normative expectations appeared to affect participants' ability to engage in physical activity, which may reflect the 'close knit' culture of the study neighbourhoods. Access to suitable local facilities and amenities such as structured and pleasant walking routes was regarded as essential. Indeed participants considered walking to be their preferred form of physical activity which may relate to the minimal skill requirement, ease of access and low financial costs incurred. Conclusion In the context of physical activity, health promoters need to be conscious of the difficulties that individuals feel in relation to bodily appearance and the pressure to comply with societal standards. This may be particularly relevant in low income settings where insufficient allocation of resources and social supports means that individuals have less opportunity to attend to physical activity than individuals living in higher income settings.